2007
DOI: 10.1021/jp0751864
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Dynamic Behavior of Cyclodextrins in Aqueous Solution

Abstract: The hydration state and dynamics of plain and chemically modified cyclodextrins (CDs) in aqueous solution were investigated by using dielectric relaxation measurements at 25 degrees C over a wide frequency range up to 20 GHz, which is the relaxation frequency of pure liquid water molecules. The obtained dielectric relaxation spectra were decomposed into two major and one minor relaxation modes with relaxation times of approximately 8.3, 20-25, and 1000-2500 ps, respectively, depending on the CD species. The tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 37 publications
7
68
1
Order By: Relevance
“…The large concentration of R-CD has an impact on water structure and thereby also on the solvation of the analyte ions. [34][35][36] It has, for example, been shown that approximately 35 water molecules are closely associated to R-CDs in solution 35 which inevitably will affect the solvation of ions. In fact, the presence of structure-creating solutes (also called kosmotropes) based on carbohydrates has previously been found to affect the permeation of analytes through lipid membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The large concentration of R-CD has an impact on water structure and thereby also on the solvation of the analyte ions. [34][35][36] It has, for example, been shown that approximately 35 water molecules are closely associated to R-CDs in solution 35 which inevitably will affect the solvation of ions. In fact, the presence of structure-creating solutes (also called kosmotropes) based on carbohydrates has previously been found to affect the permeation of analytes through lipid membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of pure and chemically modified forms of CDs in aqueous solution have also been studied recently using dielectric relaxation experiments. 24 The spectra obtained from these measurements indicate the presence of three relaxation modes with time scales of 8-10 ps, 20-25 ps, and 1-2.5 ns. In an important work, Li and McGown 25 detected the formation of nanotube aggregates of β-and γ-CDs in solution and on solid surfaces.…”
Section: Introductionmentioning
confidence: 89%
“…[20][21][22][23][24] On the contrary, less literature has regarded till now the properties of water molecules surrounding CD in aqueous solution [25][26][27] due to the difficulties to reveal separate solute and solvent dynamics, especially in case of diluted solutions. In this context, recently, depolarized light scattering has been used by some of us as a powerful tool to distinguish spectral features coming from solute rotational dynamics, hydrogen bonding solvent dynamics, and vibrational intermolecular modes of saccharides and proteins aqueous solutions (Rossi et al, submitted for publication).…”
Section: Introductionmentioning
confidence: 99%